The theoretical framework of economic integration: review and proposal - Cornejo Ramírez, Enrique (2021)
The article reviews the main definitions and theories of economic integration, emphasizing the importance and stages of the process. It also discusses the relationship of integration with national policies and new theories of integration into the global context; with particular interest is the review of the so-called new Regionalism and ECLAC’s Open Regionalism proposal. The author makes a proposal by adding to the well-known stages of economic integration presented by Bela Balassa in the early sixties of the twentieth century, an intermediate stage of integration of citizen organizations, to give it social and political content to the integrative process.